Assessment of implementation variants of conditional scalar dissipation rate in LES-CMC simulation of auto-ignition of hydrogen jet (Archives of Mechanics - Test, 2013)
In this paper the large eddy simulation (LES) and conditional moment closure (CMC) combustion model have been applied for modelling of auto-ignition of hydrogen jet issuing into a hot ambient co-flow. Most of the attention was devoted to modelling aspects of the conditional scalar dissipation rate which is a key quantity of the CMC model. Two models are compared with emphasis on differences in distributions in mixture fraction space. Analysis of mutual relations between the terms of CMC equations confirms importance of the conditional scalar dissipation rate. It is also shown that model constants are crucial from the point of view of an auto-ignition location and a flame lift off height. The numerical results are compared with experimental data and both the mean and the root mean square fluctuating values of the temperature and species mass fraction agree well with measurements.